Why are some regions rich and others poor? The impact of climate on regional income disparities - Karaca, Orhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2-4 PARK SQUARE, MILTON PARK, ABINGDON OX14 4RN, OXON, ENGLAND, 2019)
In this study, the impact of climate on regional income disparities is investigated on a sample of 10 countries. The sample includes three northern European countries (Finland, Sweden and Norway), two equatorial countries (Colombia and Brazil) and five temperate countries (Poland, Germany, France, Italy and Spain). Regression analyses have shown that population and economic activity are concentrated in relatively hot regions in cold countries, and relatively cold regions in hot countries. Climate also has a statistically significant effect on regional per capita income.
Keywords: Climate; Temperature; Regional Income Disparities; Regional Economics; iklim; Sıcaklık; Bölgesel Gelir Farklılıkları; Bölgesel İktisat